1999
DOI: 10.1557/proc-597-103
|View full text |Cite
|
Sign up to set email alerts
|

Organic Light Emitting Diode Directly Fabricated on a Polymer Waveguide Device

Abstract: Organic light emitting diodes (OLEDs) which consists of 8-hydroxyquinoline aluminum (Alq3) and diamine derivative (TPD) were directly fabricated on a polymer waveguide device. Polymer waveguide device consists of deuterated methacrylate polymer core and UV cured epoxy resin cladding. One of the edges of the polymer waveguide was cut in 45 degree, which was served as a mirror, in order to introduce the output light from OLED to the waveguide. Indium-tin oxide (ITO) or semi-transparent aluminum metal was deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…[1] Materials and devices have developed rapidly, and active matrix full color displays will become commercially available soon. [3] A number of blue-emitting materials have been synthesized, such as 5,5¢-bis(dimesitylboryl)-2,2¢-bithiophene (BMB-2T), [4] 4,4¢-bis(2,2-diphenylvinyl) biphenyl (DPVBi), [5] and 1,3-bis[4-(N,N-dimethylamino)phenyl-1,3,4-oxadiazolyl] benzene (OXD8); [6] still 9,10-bis-(b-naphthyl)-anthrene (DNA) is a very promising blue fluorescent material for its color purity and thermal stability. [3] A number of blue-emitting materials have been synthesized, such as 5,5¢-bis(dimesitylboryl)-2,2¢-bithiophene (BMB-2T), [4] 4,4¢-bis(2,2-diphenylvinyl) biphenyl (DPVBi), [5] and 1,3-bis[4-(N,N-dimethylamino)phenyl-1,3,4-oxadiazolyl] benzene (OXD8); [6] still 9,10-bis-(b-naphthyl)-anthrene (DNA) is a very promising blue fluorescent material for its color purity and thermal stability.…”
mentioning
confidence: 99%
“…[1] Materials and devices have developed rapidly, and active matrix full color displays will become commercially available soon. [3] A number of blue-emitting materials have been synthesized, such as 5,5¢-bis(dimesitylboryl)-2,2¢-bithiophene (BMB-2T), [4] 4,4¢-bis(2,2-diphenylvinyl) biphenyl (DPVBi), [5] and 1,3-bis[4-(N,N-dimethylamino)phenyl-1,3,4-oxadiazolyl] benzene (OXD8); [6] still 9,10-bis-(b-naphthyl)-anthrene (DNA) is a very promising blue fluorescent material for its color purity and thermal stability. [3] A number of blue-emitting materials have been synthesized, such as 5,5¢-bis(dimesitylboryl)-2,2¢-bithiophene (BMB-2T), [4] 4,4¢-bis(2,2-diphenylvinyl) biphenyl (DPVBi), [5] and 1,3-bis[4-(N,N-dimethylamino)phenyl-1,3,4-oxadiazolyl] benzene (OXD8); [6] still 9,10-bis-(b-naphthyl)-anthrene (DNA) is a very promising blue fluorescent material for its color purity and thermal stability.…”
mentioning
confidence: 99%
“…We demonstrated that OLEDs with fluorescent materials can be applied to fields of optical communication as electro-optical conversion devices for transmitting signals of optical digital audio and moving images. [7][8][9][10] OLEDs with various emissive materials including blue, green, yellow, and red light emissions have been investigated. Recently, phosphorescent OLEDs fabricated using phosphorescent dyes have demonstrated high external quantum efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…3) OLEDs can be expected to be applied to electrooptical conversion devices for generating highspeed optical pulses. [4][5][6][7] The doped-type OLEDs have been reported to show bright electroluminescence by Tang et al 8) The doping system is often used in OLEDs to prevent concentration quenching. The luminance is increased by doping the emission layer with highly fluorescent dyes.…”
Section: Introductionmentioning
confidence: 99%